Processing of voice signals with neural networks - Romero Muñoz, Leonardo; Fernández del Busto, Ricardo; Cervantes de Poly, Ofelia (Revista Mexicana de Ingenieria Biomedica, 1991)
A tool was developed to evaluate the application of a type of neural network, called multilayer perception, to the recognition of isolated words of voice (between one word and another a pause is made). The tool consists of a set of programs that allow to implement and analyze three speech recognition systems. The first recognition results show that the multilayer perceptron. Combined with traditional techniques. It has great potential in the development of isolated word recognition systems. (Romero 1990).